Engineering of Surfaces of Details of Machine Tool Adaptations - Erokhin V.V. (Научно-технический вестник Брянского государственного университета)
The interrelation of operational properties of the machine adaptation among themselves is considered. Qualitative interrelations between operational properties for the solution of an optimizing problem of a choice or design of the machine adaptation with the set functionality and durability are defined. The solution of an optimizing problem of design of the machine adaptation it is put concerning such operational properties as durability, contact durability, fatigue durability, rigidity, contact rigidity, wear resistance, a frettingostoykost, friction, vibrostability, tightening ability, constancy of the sizes (consideration is conducted with positions of a relaxation and creep of a material).